First international consensus statement on sports psychiatry - Claussen, Malte Christian; Currie, Alan; Koh Boon Yau, Eugene; Nishida, Masaki; Martínez, Vania; Burger, James; Creado, Shane; Schorb, Alexander; Nicola, Roberto Fernandes; Pattojoshi, Amrit; Menon, Ranjit; Glick, Ira; et al. (John Wiley and Sons, 2024)
Sports psychiatry is a young field of medicine and psychiatry that focuses on mental health among athletes, and sports and exercise within psychiatry and mental disorders. However, the development of sports psychiatry and its fields of activity vary from region to region and are not uniform yet. Sports psychiatry and the role of sports psychiatrists have also already been discussed in the field of sports and exercise medicine, and within medical teams in competitive and elite sports. A uniform definition on sports psychiatry, its fields of activity, sports psychiatrist, and the essential knowledge, skills, and abilities (plus attitudes, eKSA+A) of the sports psychiatrist were developed as part of an International Society for Sports Psychiatry (ISSP) Summit, as well as First International Consensus Statement on Sports Psychiatry. Three fields of activity can be distinguished within sports psychiatry: (i) mental health and disorders in competitive and elite sports, (ii) sports and exercise in prevention of and treatment for mental disorders, and (iii) mental health and sport-specific mental disorders in recreational sports. Each of these fields have its own eKSA+A. The definitions on sports psychiatry and sports psychiatrists, as well as the framework of eKSA+A in the different fields of activity of sports psychiatrists will help to unify and standardize the future development of sports psychiatry, establish a standard of service within sports psychiatry and together with the neighboring disciplines, and should be included into current, and future sports psychiatry education and training.